Sustainable energy management : planning, implementation, control, and strategy - Radovanovic, Mirjana (London, United Kingdom : Academic,Elsevier, 2023)
Sustainable Energy Management: Planning, Implementation, Control and Strategy, Second Edition provides the key concepts and practical knowledge needed to successfully plan, implement and control sustainable energy technologies. The book provides new paradigms for measuring energy sustainability, pragmatic methods for applying renewable resources, efficiency improvements, and unique insights on managing risk. It highlights the possible financial and practical impacts of these activities, as well as the methods for their calculation. This new edition provides updated guidelines for planning, analyzing, developing and optimizing sustainable energy production projects in the real world, also presenting real-life examples of the topics covered in each chapter. With its focus on real-life issues and discussions of practical challenges, this book is an ideal resource for engineers, researchers and energy managers developing and rolling out sustainable energy practices. Included case studies will help benchmark decisions, especially in the book's new chapter on energy security.
Previous edition: 2013.
Includes bibliographical references and index.
Keywords: Renewable energy sources; Energy development; Sustainable engineering